2010
DOI: 10.1159/000314896
|View full text |Cite
|
Sign up to set email alerts
|

Single-Port Extraperitoneal Transvesical Adenomectomy: Initial Operative Experience

Abstract: Background: Laparoscopic extraperitoneal adenomectomy is occasionally performed for symptomatic large-volume benign prostatic hyperplasia. Two different multichannel ports were used during operations. We describe the technique of single-port extraperitoneal transvesical adenomectomy and present the initial operative experience. Methods: Three patients in whom an open adenomectomy was indicated underwent single-port extraperitoneal transvesical adenomectomy. Following preparation of the extraperitoneal space vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…To avoid the basic limitations of LESS, collision of the robot's arms and small operative space, single–site instruments designed for the da Vinci ® Surgical System were used to perform single port transvesical enucleation of the prostate (STEP) [ 36 , 37 ]. In recent years, several clinical studies and case reports have been published on LESS [ 35 , 37 42 ]. Preliminary functional outcomes are encouraging, but the procedure is associated with a high risk of complications, and its role has yet to be determined [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the basic limitations of LESS, collision of the robot's arms and small operative space, single–site instruments designed for the da Vinci ® Surgical System were used to perform single port transvesical enucleation of the prostate (STEP) [ 36 , 37 ]. In recent years, several clinical studies and case reports have been published on LESS [ 35 , 37 42 ]. Preliminary functional outcomes are encouraging, but the procedure is associated with a high risk of complications, and its role has yet to be determined [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…La hiperplasia prostática benigna (HPB) es una de las principales causas de retención urinaria y es la causa más común de sintomatología del tracto urinario inferior en alrededor del 60% de los hombres de 60 años de edad o mayores 1 . Aproximadamente 3 de cada 10 pacientes son candidatos a tratamiento quirúrgico 2 .…”
Section: Introductionunclassified
“…Hoepffner et al, in their study with the biggest series published, reported 100 patients' results with mean prostate weight of 97.1 ± 18.5 g, mean operation time 66.3 ± 12.3 min with blood loss of 250 ± 86.8 ml without the need of blood transfusion with mean hospital stay of 4.2 ± 1.3 days and mean catheterization time of 3.2 ± 1 days[38]. Oktay et al reported the results of 16 LSP patients with the biggest prostate weight, 147 g (between 80 and 200 g), mean operation time 133 min (75-210 min), mean blood loss 134 ml (50-300 ml) requiring one transfusion, hospital stay 3.9 days (2-7 days), and catheterization duration of 6.3 (6-7) days[39].Chlosta et al., in their series of 66 patients, reported surgery time of 55 (45-85) minutes as the shortest surgery time and similar results for blood loss, hospital stay, and catheterization time[40].…”
mentioning
confidence: 99%